The return of ancestral gods: modern Ukrainian Paganism as an alternative vision for a nation - Lesiv, Mariya (McGill-Queen's studies in the history of religion. Series two, 2013)
1 "Living with Honour": Modern Western Paganism -- 2 "Where Do They Get This From?": Sources of Ukrainian Paganism -- 3 Ukrainian Pagan Groups: History, Ideology, and Spirituality -- 4 Boundaries and Borders: Cultural Context -- 5 "We Haven't Given Up What Is Ours": Past and Present -- 6 Glory to Dazhboh (Sun-God) or to All Native Gods?: Monotheism and Polytheism -- 7 "Where Else Is There Such a People?": Vision for a Nation -- 8 "We Allowed Nature to Live in Our Holy Place": Nature and Power -- 9 "This Is Indeed Ours!": Religious Syncretism -- 10 In Spite of Politics: Aesthetics and Beauty.